2021
DOI: 10.1101/2021.02.01.429171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MESOMELIC DYSPLASIAS ASSOCIATED WITH THEHOXDLOCUS ARE CAUSED BY REGULATORY REALLOCATIONS

Abstract: Some human families display severe shortening and bending of the radius and ulna, a condition referred to as mesomelic dysplasia. Many of these families contain chromosomal rearrangements at 2q31, where the human HOXD locus maps. In mice, the dominant X-ray-induced Ulnaless inversion of the HoxD gene cluster produces a similar phenotype suggesting that the same mechanism is responsible for this pathology in humans and mice. Amongst the proposed explanations, the various alterations to the genomic structure of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…We next asked whether these changes in expression were due to reallocations in interactions between the genes and their regulatory landscapes. We performed Capture Hi-C in micro-dissected proximal forelimb cells of the Del(CBS1), Del(CBS1-3) and Del(CBS1-5) alleles and compared them with control samples (Bolt et al, 2021). In the Del(CBS1) allele, we observed a minor loss of interaction with the CS38-40 T-DOM sub-TAD boundary and a gain of ectopic interactions with T-DOMa, as seen on the subtraction maps (Fig.…”
Section: Effects Of Cbs Disruptions Upon Hoxd Gene Regulation In Developing Proximal Limb Budsmentioning
confidence: 83%
See 1 more Smart Citation
“…We next asked whether these changes in expression were due to reallocations in interactions between the genes and their regulatory landscapes. We performed Capture Hi-C in micro-dissected proximal forelimb cells of the Del(CBS1), Del(CBS1-3) and Del(CBS1-5) alleles and compared them with control samples (Bolt et al, 2021). In the Del(CBS1) allele, we observed a minor loss of interaction with the CS38-40 T-DOM sub-TAD boundary and a gain of ectopic interactions with T-DOMa, as seen on the subtraction maps (Fig.…”
Section: Effects Of Cbs Disruptions Upon Hoxd Gene Regulation In Developing Proximal Limb Budsmentioning
confidence: 83%
“…All four mammalian Hox clusters are partitioned in between two TADs, with a boundary systematically isolating the most posterior group 13 Hox gene from the others. Group 13 Hox genes are coding for proteins that participate to the morphogenesis of terminal structures and hence embryo development must be protected from the action of such proteins, which can abrogate axial extension (Young et al, 2009) or affect proper morphogenesis (Bolt et al, 2021;Darbellay et al, 2019) through their dominant negative function over other HOX proteins. This isolation is achieved through the positioning of Hox13 genes into a different TAD, thus making them unresponsive to the numerous enhancer sequences acting upon other Hox genes during development.…”
Section: Cbss In the Making Of The Tad Boundary At The Hoxd Clustermentioning
confidence: 99%
“…Sheth et al [2014]; Beccari et al [2016]; Kherdjemil et al [2016] showed that Hoxd13 represses the transcription of Hoxa11 in the embryonic distal limb leading to two distinct domains of expression. We use the scRNA-seq from Bolt et al [2021] which has been generated from embryonic forelimbs. A clustering analysis revealed 17 clusters.…”
Section: Estimating the Distribution Of Expression Values Of Amentioning
confidence: 99%
“…A clustering analysis revealed 17 clusters. Using Hoxd13 as a marker, 4 clusters (3,4,5,9) were attributed to the distal part of the limb [see Bolt et al, 2021]. Unexpectedly, Hoxa11 was not totally absent from these clusters.…”
Section: Estimating the Distribution Of Expression Values Of Amentioning
confidence: 99%
“…While genomic rearrangements altering the structure of TADs were reported to impact proper gene regulation during development leading to genetic syndromes (e.g. (Bolt et al, 2021; Lupiáñez et al, 2015), in most cases, these rearrangements also affected enhancer-promoter spatial relationships, which makes a causal assessment difficult.…”
Section: Introductionmentioning
confidence: 99%